Procedural Protection of Fundamental Rights in the Peruvian Constitution of 1979. - García Belaúnde, Domingo (1981)
The protection of fundamental rights is an essential task for any state. It is therefore essential to be aware of the procedural measures that can be applied when constitutionally recognised rights are affected. With this in mind, the purpose of this article is to provide a detailed description of the procedural measures and constitutional control mechanisms included in the Peruvian Constitution of 1979 to guarantee the effective protection of fundamental rights. Among the protective measures, the so-called constitutional guarantees stand out: amparo, habeas corpus, popular action and action for unconstitutionality, to which should be added the contentious-administrative action. The report also assesses, albeit to a lesser extent, exceptional regimes and their impact on fundamental rights. Mention is also made of the ability of the Court of Constitutional Guarantees to review in cassation the rejection of decisions taken in habeas corpus and amparo proceedings, once the judicial process has been exhausted. Finally, Finally, the right to appeal to international courts or organizations after having exhausted domestic remedies is indicated.